Analysis of Grain Production in the Industrial Management System of EurAsEC Countries - TUYAKOVA, Zauresh; SARSEMBAEVA, Gulmira; DYUZELBAEVA, Gulnara; KUKHAR, Viktor (Journal of Environmental Management and Tourism, 2019)
This article presents the results of analysis of the grain industry state of the Russian Federation and the Republic of Kazakhstan in comparison with the forecast and actual changes in the volumes of world production and sale of grain. A comparative analysis of the gross grain harvest and its structure, the dynamics of planting areas changes and the yield of wheat, as well as the structure of grain production prime cost, was carried out using the example of the most typical regions bordering each other - the Orenburg and Kostanay regions. The management accounting system, in particular its production accounting subsystem, is adapted to the conditions of a particular enterprise, which must be developed on the basis of management goals and capabilities. It should be noted that all the basic elements of management accounting were widely used in domestic practice. However, the lack of interest of workers in improving production efficiency did not allow to obtain the proper effect from the use of these elements. The generalization of European and domestic economic experience allows us to conclude that management accounting currently allows successfully implement the functions of accounting, planning, control and regulation of the cost of production - one of the most important indicators of the economic entity.